A new peptide ligand for targeting human carbonic anhydrase IX, identified through the phage display technology - Askoxylakis, Vasileios; Garcia Boy, Regine; Rana, Shoaib; Krämer, Susanne; Hebling, Ulrike; Mier, Walter; Altmann, Annette; Markert, Annette; Debus, Jürgen; Haberkorn, Uwe (PLOS ONE, 2010)
Carbonic anhydrase IX (CAIX) is a transmembrane enzyme found to be overexpressed in various tumors and associated with tumor hypoxia. Ligands binding this target may be used to visualize hypoxia, tumor manifestation or treat tumors by endoradiotherapy. Methods Phage display was performed with a 12 amino acid phage display library by panning against a recombinant extracellular domain of human carbonic anhydrase IX. The identified peptide CaIX-P1 was chemically synthesized and tested in vitro on various cell lines and in vivo in Balb/c nu/nu mice carrying subcutaneously transplanted tumors. Binding, kinetic and competition studies were performed on the CAIX positive human renal cell carcinoma cell line SKRC 52, the CAIX negative human renal cell carcinoma cell line CaKi 2, the human colorectal carcinoma cell line HCT 116 and on human umbilical vein endothelial cells (HUVEC). Organ distribution studies were carried out in mice, carrying SKRC 52 tumors. RNA expression of CAIX in HCT 116 and HUVEC cells was investigated by quantitative real time PCR. Results In vitro binding experiments of 125I-labeled-CaIX-P1 revealed an increased uptake of the radioligand in the CAIX positive renal cell carcinoma cell line SKRC 52. Binding of the radioligand in the colorectal carcinoma cell line HCT 116 increased with increasing cell density and correlated with the mRNA expression of CAIX. Radioligand uptake was inhibited up to 90% by the unlabeled CaIX-P1 peptide, but not by the negative control peptide octreotide at the same concentration. No binding was demonstrated in CAIX negative CaKi 2 and HUVEC cells. Organ distribution studies revealed a higher accumulation in SKRC 52 tumors than in heart, spleen, liver, muscle, intestinum and brain, but a lower uptake compared to blood and kidney. Conclusions These data indicate that CaIX-P1 is a promising candidate for the development of new ligands targeting human carbonic anhydrase IX.
Gesehen am 25.11.2022